An ex vivo physiologic and hyperplastic vessel culture model to study intra-arterial stent therapies. (August 2021) - Wang, Juan; Kural, Mehmet H.; Wu, Jonathan; Leiby, Katherine L.; Mishra, Vinayak; Lysyy, Taras; Li, Guangxin; Luo, Jiesi; Greaney, Allison; Tellides, George; Qyang, Yibing; Huang, Nan; et al.
Abstract: Conventional in vitro methods for biological evaluation of intra-arterial devices such as stents fail to accurately predict cytotoxicity and remodeling events. An ex vivo flow-tunable vascular bioreactor system (VesselBRx), comprising intra- and extra-luminal monitoring capabilities, addresses these limitations. VesselBRx mimics the in vivo physiological, hyperplastic, and cytocompatibility events of absorbable magnesium (Mg)-based stents in ex vivo stent-treated porcine and human coronary arteries, with in-situ and real-time monitoring of local stent degradation effects. Unlike conventional, static cell culture, the VesselBRx perfusion system eliminates unphysiologically high intracellular Mg 2+ concentrations and localized O2 consumption resulting from stent degradation. Whereas static stented arteries exhibited only 20.1% cell viability and upregulated apoptosis, necrosis, metallic ion, and hypoxia-related gene signatures, stented arteries in VesselBRx showed almost identical cell viability to in vivo rabbit models (~94.0%). Hyperplastic intimal remodeling developed in unstented arteries subjected to low shear stress, but was inhibited by Mg-based stents in VesselBRx, similarly to in vivo . VesselBRx represents a critical advance from the current static culture standard of testing absorbable vascular implants.